(2E)-1-(2-Bromophenyl)-3-(4-bromophenyl)prop-2-en-1-one - Jerry P. Jasinski; Ray J. Butcher; K. Veena; B. Narayana; H. S. Yathirajan (Acta Crystallographica Section E, 2010)
The title compound, C15H10Br2O, is a chalcone with 2-bromophenyl and 4-bromophenyl rings bonded to opposite sides of a propenone group. The dihedral angle between mean planes of the benzene rings is 71.3 (1)°. The angle between the mean plane of the prop-2-ene-1-one group and the mean planes of the 2-bromophenyl and 4-bromophenyl rings are 64.2 (9) and 71.3 (1)°, respectively. A weak intermolecular C—H...O interaction and two weak C—Br...π interactions are observed, which contribute to the stability of the crystal packing.